Desert Lawmen : The High Sheriffs of New Mexico and Arizona Territories, 1846-1912 - Ball, Larry D., 1940- (Book collections on Project MUSE., 1996)
An historical survey of frontier lawmen in territorial New Mexico and Arizona reveals that sheriffs were generally elected to four year terms, defended settlers and protected their property from violence, and performed other duties ranging from tracking down stagecoach robbers and serving court warrants to locking up drunks and quelling domestic disputes.